Research hotspots and trends of skin barrier in atopic dermatitis in the past 24-year: a bibliometric analysis - Fangchang Huang; Fangchang Huang; Xin Zhu; Xin Zhu; Xinglong Liang; Xinglong Liang (Frontiers in Medicine, 2025)
BackgroundAtopic dermatitis (AD) is a chronic, pruritic, inflammatory skin condition that imposes significant psychological and economic burdens on patients due to its recurring nature. Its etiology is multifactorial, involving interactions between genetic predispositions and environmental factors. The skin barrier serves as both a mechanical and immunological defense, and its structural damage and functional impairments significantly contribute to the pathogenesis of AD. This study aims to explore the future prospects and developmental trends of the skin barrier in the context of AD through a bibliometric analysis.ObjectiveTo analyze the research status, hot spots and development trend of skin barrier in AD.MethodsRelevant studies were extracted from the Web of Science database and screened by researchers, with bibliometric analysis conducted using VOSviewer, CiteSpace, and other tools.ResultsA total of 4,227 publications were identified over a 24-year research period. The United States is the leading contributor, with 1,263 publications, and demonstrates extensive collaboration with numerous countries. The journal with the highest number of publications is the Journal of Allergy and Clinical Immunology. The most prolific institutions is the University of California, San Francisco. Recent years have seen high citation intensity for keywords such as “dupilumab,” “barrier dysfunction,” and “gut microbiota”.ConclusionThe mechanism of the skin barrier in AD remains an area requiring ongoing research and analysis. Although significant progress has been achieved, future research will benefit from advancements in technology.